Effect of Dietary Supplement Mixed with Probiotics on Body Weight and Age of Honeybee (Apis mellifera) - Yooboriboon, Somsak; Chuenchan, Wanida; Sumpaoloi, Thanaphong (Journal of Science Ladkrabang, 2023)
The objective of this research was to study the effect of dietary supplement mixed with probiotics on body weight and age of honeybee (Apis mellifera) workers. Four species of probiotics, Lactobacillus casei TISTR 390, L. plantarum TISTR 541, L. curvatus TISTR 938 and L. acidophilus TISTR 2365 were used in this study. A random sampling of marked workers beginning from coming out of the comb was performed. Honeybee samples of 100 workers per hive were weighed every week for 8 weeks. Five hives were investigated for each experiment. The average body weight per worker was calculated. To find the average age of workers, acrylic color was painted on thorax of newly born workers with 300 workers per hive. The number of worker bees that were marked daily for 80 days, was counted in 5 hives per experiment. The results showed that in the last week of this research, the worker bees fed by natural foods had the highest average body weight with 113.76 ± 24.88 mg which showed significant differences with other experimental results, followed by the honeybee group with dietary supplement mixed with L. casei (101.36 ± 15.23 mg), L. curvatus (96.78 ± 12.69 mg), L. plantarum (95.66±15.29 mg), L. acidophilus (93.52 ± 14.61 mg), and the group fed without probiotics (92.62 ± 12.84 mg), respectively [F (5, 144) = 5.729, p≤0.05]. In addition, the age of worker bees fed with dietary supplement mixed with all probiotics showed significant difference from those without probiotics. The highest age of workers was found in the honeybee workers fed with dietary supplement mixed with L. plantarum (67.40 ± 0.548 days), followed by those with L. curvatus (66.80 ± 0.447 days), without probiotics (51.80 ± 0.447 days) and with natural foods (42.60 ± 0.548 days), respectively [F (5, 24) = 2245.80, p≤0.05]. The research indicated that all four species of probiotics can be progressively developed to be a mixture in supplementary diet to enhance honeybee age.